Colour characteristics of soppressata obtained from Casertana pig autochthonous ancient genetic type (AAGT) - Barone C.M.A.; Castellano N.; Gigante G.; Liguori L.; Occidente M.; Matassino D. (Mediterranean livestock production: uncertainties and opportunities, 2008)
The aim of the research was to investigate colour characteristics of soppressata stored for 45 and 90 days under vacuum and under perirenal fat. The products were obtained from 20 pigs (10 castrated males and 10 entire females) belonging to AAGT Casertana, reared in multiple boxes at ConSDABI experimental farm. For each soppressata the colorimetric profile was determined on 7-8 samples by using spectrophotometer (U3000, Hitachi) equipped with integrated sphere. The results showed that: (i) castrated males provide a product with higher redness value (a*) and a lower hue value at 45 days if stored under perirenal fat, while the females showed higher yellowness value (b*) when stored under vacuum; and (ii) at 90 days of storage the differences in the colour characteristics are confirmed.
2. Seminar of the Scientific-Professional Network on Mediterranean Livestock Farming (RME), 2006/05/18-20, Zaragoza, (Spain)